Tunable Photocatalytic Properties of Au-Decorated BiFeO3 Nanostructures for Dye Photodegradation - Wu, Jhen-Yang; Chen, Chun-Yi; Wang, Junan; Jin, Xinyu; Hou, Wending; Kuo, Hsuan-Hung; Chiu, Wan-Ting; Kurioka, Tomoyuki; Sone, Masato; Okamoto, Satoshi; Hsu, Yung-Jung; Chang, Tso-Fu Mark (ACS applied nano materials, 2024)
This study presents the synthesis and characterization of Au nanoparticle-decorated BiFeO3 (Au-BiFeO3) nanocrystals fabricated by a hydrothermal technique. The key focus is the augmented photocatalytic properties of these nanocrystals for the effective photodegradation of methylene blue (MB), a common industrial dye. The magnetic properties of the Au-BiFeO3 merely differ from those of the BiFeO3. The decoration of Au nanoparticles onto the BiFeO3 introduces heterojunction structures that lead to effective charge-carrier separation under illumination. Time-resolved photoluminescence spectroscopy confirms the enhanced charge separation and reduced recombination rate in Au-BiFeO3 nanocrystals. Through meticulous optimization, the photocatalytic performance of these nanocomposites was evaluated under various Au loadings, revealing that 1.0 wt % Au-BiFeO3 exhibits the most superior activity, achieving an impressive 98% degradation efficiency of MB under a 500 W xenon lamp within 120 min. The study also demonstrates the structural integrity and stability of the photocatalyst, with it retaining about 80% of its original activity after four cycles of the 120 min photodegradation process. These findings suggest that the Au-BiFeO3 nanocrystals are promising, efficient, and sustainable photocatalysts for environmental purification and offer insights into designing advanced materials for solar energy utilization.